Sleep and behavioral problems in Down syndrome: differences between school age and adolescence - Fucà, Elisa; Costanzo, Floriana; Celestini, Laura; Galassi, Paolo; Villani, Alberto; Valentini, Diletta; Vicari, Stefano (Frontiers in Psychiatry, 2023)
Individuals with Down syndrome (DS) are at risk for sleep problems. In spite of the well-established knowledge on the presence of sleep difficulties in DS and the associated emotional and behavioral problems, less is known about possible differences in the kind of associations between sleep and emotional/behavioral problems across different age ranges. We included in this retrospective study 289 participants with DS aged 6-18 years with the aims to explore differences in the distribution of sleep problems between specific age groups (school-age vs adolescence) and to identify specific age-based associations between sleep problems and emotional/behavioral problems. Some differences in the distribution of sleep problems emerged between age groups. Moreover, differences in the patterns of association between emotional/behavioral difficulties and sleep problems - in particular sleep-related breathing difficulties and parasomnias – have been observed. On the other hand, sleep-wake transition disorders and excessive daily somnolence appear to be generally related with emotional and behavioral problems (both internalizing and externalizing) across school age and adolescence. These results remark the importance of appropriate neuropsychiatric and psychological evaluation taking into account age-specific needs and features of individuals with DS.